The Dynamics of Laying Hens Business in Sumberjo Village, Kademangan District, Blitar Regency, East Java, Indonesia During the Covid-19 Pandemic - Lailatul, Oxsy; Haryuni, Nining; Lestariningsih, Lestariningsih (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Nahdlatul Ulama Blitar, 2024)
The purpose of this study was to determine the dynamics of the laying hens business during the Covid-19 pandemic in Sumberjo Village, Kademangan District, Blitar Regency, East Java, Indonesia. The method used in this study is a descriptive quantitative approach with survey techniques using questionnaires. Respondents used in this study were 35 egg laying breeders. Determination of respondents in this study was carried out by purposive sampling. Data collection in this study was carried out through observation and surveys using questionnaires. The results of statistical analysis showed that the average farmers in Sumberjo Village, Kademangan District were small breeders where 28.57% had a junior high school education. In their business activities, 73% of respondents replace livestock by maintaining DOC and 66% of respondents use factory feed supplied by poultry shops in Blitar Regency. During the Covid-19 pandemic, supplying animal feed and selling eggs became difficult and business profits were difficult to obtain. A score for the difficulty level of feed supply was 485.00; difficulty in selling chicken eggs was 491.00 and difficulty in earning profits in the laying hens business was 500.00. The conclusion of this study is that there are dynamics in the laying hens business in Sumberjo Village, Kademangan District during the Covid-19 pandemic where there are difficulties in feed supply, egg sales and achieving business profits.